2019 IEEE European Symposium on Security and Privacy (EuroS&P) 2019
DOI: 10.1109/eurosp.2019.00038
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Location Privacy for Unknown Mobility Behaviors

Abstract: Location Privacy-Preserving Mechanisms (LPPMs) in the literature largely consider that users' data available for training wholly characterizes their mobility patterns. Thus, they hardwire this information in their designs and evaluate their privacy properties with these same data. In this paper, we aim to understand the impact of this decision on the level of privacy these LPPMs may offer in real life when the users' mobility data may be different from the data used in the design phase. Our results show that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 23 publications
(86 reference statements)
2
30
0
Order By: Relevance
“…In fact, it has been discussed that the definition of in geoindistinguishability may be misleading in terms of the privacy level [13]. In contrast with [12], our results showed that the relation between the average quality loss and average adversary error is only linear after a non-negligible threshold. That is, there exists an upper bound on the value of the privacy budget necessary to guarantee relevant privacy protection, which in our setting was = 4 km −1 .…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…In fact, it has been discussed that the definition of in geoindistinguishability may be misleading in terms of the privacy level [13]. In contrast with [12], our results showed that the relation between the average quality loss and average adversary error is only linear after a non-negligible threshold. That is, there exists an upper bound on the value of the privacy budget necessary to guarantee relevant privacy protection, which in our setting was = 4 km −1 .…”
Section: Introductionmentioning
confidence: 54%
“…As in previous relevant works [7,10,12,14,17], we shall consider a user of an LBS which reports his location to the LBS provider to obtain information. We consider as adversary any entity with access to the location reports attempting to infer private information [2,16], including the LBS provider or any passive eavesdropper.…”
Section: Problem Definitionmentioning
confidence: 99%
See 3 more Smart Citations